- Perbandingan Melampirkan Video Unboxing Klaim Ganti Kerugian Di Indonesia Dan Korea Selatan: - - Klaura Dwi Kinasih; Dian Purnamasari (Faculty of Law, Universitas Trisakti, 2023)
In Indonesia, many of consumers receive goods not in accordance with what was promised. This is the basis for submitting compensation claims in Indonesian marketplace, there is an obligation to attach video unboxing. Unlike South Korea, the marketplace does not require an unboxing video to be attached for compensation claims. The problem raise is how the difference is in the implementation of the need for video unboxing for compensation claims submitted by consumers in Indonesia and South Korea. The research method is carried out normatively, using secondary data supplemented by interview results. The results of this research, discussion and conclusion show that consumers in Indonesia have an obligation to attach video unboxing for compensation claims, in contrast to consumers in South Korea who have no obligation to attach video unboxing for compensation claims.